Organisation of Lublin confinement institutions in 1939–1944 within the ramifications of the German security apparatus - Michniowski, Marcin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The aim of the article is to present the confinement institutions set up in Lublin in 1939–1944 by the German occupier, and to analyse the organisational aspects of their functioning in the operational context of various agencies of the security system of the Third Reich and the General Government. The first part of the essay consists of background information necessary to conduct the analysis – exposition of the administrational division of Polish territory after the September campaign and the structure of the security apparatus introduced by the German occupier. In the main body, three main stages of establishment of the confinement institutions are outlined, based on the comparison of the circumstances influencing their formation. Simultaneously, their official subordination to appropriate agencies of the security system is shown, what is compared to the actual dominance of various parties over different prisons and camps. As such, it is possible to present the whole segment of the German occupational system, from two distinctive perspectives: existence of a series of suitable institutions serving specific roles in order to strengthen the occupier’s control over the Polish population, and the competition of respective agencies of the German security apparatus over the masses of prisoners.

Celem artykułu jest przedstawienie instytucji odosobnienia utworzonych w Lublinie w latach 1939–1944 przez okupanta niemieckiego oraz przeprowadzenie analizy aspektów organizacyjnych ich funkcjonowania w kontekście działania poszczególnych organów systemu bezpieczeństwa III Rzeszy i Generalnego Gubernatorstwa. Pierwsza część zawiera podstawowe informacje niezbędne do przeprowadzenia badania – zaprezentowanie podziału administracyjnego ziem polskich po kampanii wrześniowej oraz struktury aparatu bezpieczeństwa wprowadzonego przez niemieckiego okupanta. W części właściwej analizy nakreślono trzy główne etapy tworzenia instytucji odosobnienia, co osiągnięto na podstawie porównania okoliczności wpływających na ich założenie. Jednocześnie zaprezentowano ich oficjalną pozycję w strukturach organów systemu bezpieczeństwa, co zestawiono z faktyczną dominacją różnych agencji i postaci nad poszczególnymi obozami i więzieniami. W ten sposób przedstawiono cały odcinek niemieckiego systemu okupacyjnego z dwóch odrębnych perspektyw: utworzenia szeregu odpowiednich instytucji pełniących określone role w celu wzmocnienia kontroli okupanta nad ludnością polską oraz konkurencji poszczególnych agencji niemieckiego aparatu bezpieczeństwa o kontrolę nad masami więźniów.
Keywords: Nazi prisons; Nazi camps; Nazi occupation; World War II; KL Lublin; Majdanek; Lublin Castle; więzienia hitlerowskie; obozy hitlerowskie; okupacja hitlerowska; II wojna światowa; Zamek Lubelski